Simulations of Biomolecules in Electrolyte Solutions. Issue 4 (15th January 2019) - Friedman, Ran
Abstract: Biomolecules including proteins, lipid membranes, and nucleic acids operate at an aqueous milieu that includes solvated ions. The interactions with ions affect biomolecules in different ways depending on the nature of the solute and the type of the ions. The dynamic nature of small soluble ions makes it difficult to follow them by structural methods. Consequently, theories were developed to explain how biomolecules interact in an environment that includes electrolytes. Moreover, simulations studies are often used to study such systems at the molecular or atomistic level. The status of the field, and in particular of simulation studies, is the subject of this progress report. Abstract : Biomolecules (such as proteins, lipids, and nucleic acids) operate at electrolyte solutions, and some of their properties depend on the solvated ions. Simulations and theories that are used to study how ions interact with biomolecules are the subject of this report.